Access to sexual and reproductive health commodities in East and Southern Africa: a cross-country comparison of availability, affordability and stock-outs in Kenya, Tanzania, Uganda and Zambia - Gaby I. Ooms; Denis Kibira; Tim Reed; Hendrika A. van den Ham; Aukje K. Mantel-Teeuwisse; Gemma Buckland-Merrett (BMC, 2020)
Abstract Background Access to sexual and reproductive health services continues to be a public health concern in Kenya, Tanzania, Uganda and Zambia: use of modern contraceptives is low, and unmet family planning needs and maternal mortality remain high. This study is an assessment of the availability, affordability and stock-outs of essential sexual and reproductive health commodities (SRHC) in these countries to inform interventions to improve access. Methods The study consisted of an adaptation of the World Health Organization/Health Action International methodology, Measuring Medicine Prices, Availability, Affordability and Price Components. Price, availability and stock-out data was collected in July 2019 for over fifty lowest-priced SRHC from public, private and private not-for-profit health facilities in Kenya (n = 221), Tanzania (n = 373), Uganda (n = 146) and Zambia (n = 245). Affordability was calculated using the wage of a lowest-paid government worker. Accessibility was illustrated by combining the availability (≥ 80%) and affordability (less than 1 day's wage) measures. Results Overall availability of SRHC was low at less than 50% in all sectors, areas and countries, with highest mean availability found in Kenyan public facilities (46.6%). Stock-outs were common; the average number of stock-out days per month ranged from 3 days in Kenya's private and private not-for-profit sectors, to 12 days in Zambia's public sector. In the public sectors of Kenya, Uganda and Zambia, as well as in Zambia's private not-for-profit sector, all SRHC were free for the patient. In the other sectors unaffordability ranged from 2 to 9 SRHC being unaffordable, with magnesium sulphate being especially unaffordable in the countries. Accessibility was low across the countries, with Kenya's and Zambia's public sectors having six SRHC that met the accessibility threshold, while the private sector of Uganda had only one SRHC meeting the threshold. Conclusions Accessibility of SRHC remains a challenge. Low availability of SRHC in the public sector is compounded by regular stock-outs, forcing patients to seek care in other sectors where there are availability and affordability challenges. Health system strengthening is needed to ensure access, and these findings should be used by national governments to identify the gaps and shortcomings in their supply chains.